Accuracy assessment of global internal-tide models using satellite altimetry - Loren Carrere; Brian K. Arbic; Brian Dushaw; Gary Egbert; Svetlana Erofeeva; Florent Lyard; Richard D. Ray; Clément Ubelmann; Edward Zaron; Zhongxiang Zhao; Jay F. Shriver; Maarten Cornelis Buijsman; et al. (Ocean Science, 2021)
Altimeter measurements are corrected for several geophysical parameters in order to access ocean signals of interest, like mesoscale or sub-mesoscale variability. The ocean tide is one of the most critical corrections due to the amplitude of the tidal elevations and to the aliasing phenomena of high-frequency signals into the lower-frequency band, but the internal-tide signatures at the ocean surface are not yet corrected globally. Internal tides can have a signature of several centimeters at the surface with wavelengths of about 50–250 km for the first mode and even smaller scales for higher-order modes. The goals of the upcoming Surface Water Ocean Topography (SWOT) mission and other high-resolution ocean measurements make the correction of these small-scale signals a challenge, as the correction of all tidal variability becomes mandatory to access accurate measurements of other oceanic signals. In this context, several scientific teams are working on the development of new internal-tide models, taking advantage of the very long altimeter time series now available, which represent an unprecedented and valuable global ocean database. The internal-tide models presented here focus on the coherent internal-tide signal and they are of three types: empirical models based upon analysis of existing altimeter missions, an assimilative model and a three-dimensional hydrodynamic model. A detailed comparison and validation of these internal-tide models is proposed using existing satellite altimeter databases. The analysis focuses on the four main tidal constituents: M2, K1, O1 and S2. The validation process is based on a statistical analysis of multi-mission altimetry including Jason-2 and Cryosphere Satellite-2 data. The results show a significant altimeter variance reduction when using internal-tide corrections in all ocean regions where internal tides are generating or propagating. A complementary spectral analysis also gives some estimation of the performance of each model as a function of wavelength and some insight into the residual non-stationary part of internal tides in the different regions of interest. This work led to the implementation of a new internal-tide correction (ZARON'one) in the next geophysical data records version-F (GDR-F) standards.

Corrigendum to "NEMO on the shelf: assessment of the Iberia–Biscay–Ireland configuration" published in Ocean Sci., 9, 745–771, 2013 - C. Maraldi; J. Chanut; B. Levier; N. Ayoub; P. De Mey; G. Reffray; F. Lyard; S. Cailleau; M. Drévillon; E. A. Fanjul; M. G. Sotillo; P. Marsaleix (Ocean Science, 2013)

NEMO on the shelf: assessment of the Iberia–Biscay–Ireland configuration - C. Maraldi; J. Chanut; B. Levier; N. Ayoub; P. De Mey; G. Reffray; F. Lyard; S. Cailleau; M. Drévillon; E. A. Fanjul; M. G. Sotillo; P. Marsaleix (Ocean Science, 2013)
This work describes the design and validation of a high-resolution (1/36°) ocean forecasting model over the "Iberian–Biscay–Irish" (IBI) area. The system has been set-up using the NEMO model (Nucleus for European Modelling of the Ocean). New developments have been incorporated in NEMO to make it suitable to open- as well as coastal-ocean modelling. In this paper, we pursue three main objectives: (1) to give an overview of the model configuration used for the simulations; (2) to give a broad-brush account of one particular aspect of this work, namely consistency verification; this type of validation is conducted upstream of the implementation of the system before it is used for production and routinely validated; it is meant to guide model development in identifying gross deficiencies in the modelling of several key physical processes; and (3) to show that such a regional modelling system has potential as a complement to patchy observations (an integrated approach) to give information on non-observed physical quantities and to provide links between observations by identifying broader-scale patterns and processes. We concentrate on the year 2008. We first provide domain-wide consistency verification results in terms of barotropic tides, transports, sea surface temperature and stratification. We then focus on two dynamical subregions: the Celtic shelves and the Bay of Biscay slope and deep regions. The model–data consistency is checked for variables and processes such as tidal currents, tidal fronts, internal tides and residual elevation. We also examine the representation in the model of a seasonal pattern of the Bay of Biscay circulation: the warm extension of the Iberian Poleward Current along the northern Spanish coast (Navidad event) in the winter of 2007–2008.

Three-dimensional modelling of wave-induced current from the surf zone to the inner shelf - H. Michaud; P. Marsaleix; Y. Leredde; C. Estournel; F. Bourrin; F. Lyard; C. Mayet; F. Ardhuin (Ocean Science, 2012)
We develop and implement a new method to take into account the impact of waves into the 3-D circulation model SYMPHONIE (Marsaleix et al., 2008, 2009a) following the simplified equations of Bennis et al. (2011) which use glm2z-RANS theory (Ardhuin et al., 2008c). These adiabatic equations are completed by additional parameterizations of wave breaking, bottom friction and wave-enhanced vertical mixing, making the forcing valid from the surf zone through to the open ocean. The wave forcing is performed by wave generation and propagation models WAVEWATCH III® (Tolman, 2008, 2009; Ardhuin et al., 2010) and SWAN (Booij et al., 1999). The model is tested and compared with other models for a plane beach test case, previously tested by Haas and Warner (2009)and Uchiyama et al. (2010). A comparison is also made with the laboratory measurements of Haller et al. (2002) of a barred beach with channels. Results fit with previous simulations performed by other models and with available observational data. Finally, a realistic case is simulated with energetic waves travelling over a coast of the Gulf of Lion (in the northwest of the Mediterranean Sea) for which currents are available at different depths as well as an accurate bathymetric database of the 0–10 m depth range. A grid nesting approach is used to account for the different forcings acting at different spatial scales. The simulation coupling the effects of waves and currents is successful to reproduce the powerful northward littoral drift in the 0–15 m depth zone. More precisely, two distinct cases are identified: When waves have a normal angle of incidence with the coast, they are responsible for complex circulation cells and rip currents in the surf zone, and when they travel obliquely, they generate a northward littoral drift. These features are more complicated than in the test cases, due to the complex bathymetry and the consideration of wind and non-stationary processes. Wave impacts in the inner shelf are less visible since wind and regional circulation seem to be the predominant forcings. Besides, a discrepancy between model and observations is noted at that scale, possibly linked to an underestimation of the wind stress. This three-dimensional method allows a good representation of vertical current profiles and permits the calculation of the shear stress associated with waves and currents. Future work will focus on the combination with a sediment transport model.

Ocean tide loading (OTL) displacements from global and local grids: comparisons to GPS estimates over the shelf of Brittany, France - Stavros A. Melachroinos; R. Biancale; M. Llubes; F. Perosanz; F. Lyard; M. Vergnolle; M. -N. Bouin; F. Masson; J. Nicolas; L. Morel; S. Durand (Journal of Geodesy, 2008)